Why a few agricultural cooperatives survived the crisis in the cooperative movement in Uganda while many others collapsed - Kwapong, Nana Afranaa; Korugyendo, Patrick Lubega (International Food Policy Research Institute, 2010)
Agricultural cooperatives in Uganda date back to 1913 as a response to the disadvantageous terms of trade imposed on smallholder farmers by colonial administrators and middlemen who monopolized both domestic and export markets for coffee and cotton (Kabuga and Kitandwe 1995; Kyazze 2010; Mugisha et al. 2005; Flygare 2006). In such an economic context, forming a farmers' cooperative provided a mechanism for smallholders to collectively bargain for higher output prices, achieve higher margins through economies of scale, and engage in value-added activities. Until the 1980s, cooperatives in Uganda had some success in counteracting the effects of unfavorable market positions for smallholder farmers. At that time, political instability, the liberalization of markets, and mismanagement, among other reasons, caused almost all to fail. However, a few cooperatives survived. This brief summarizes case studies that examine the underlying factors that resulted in the survival of some cooperatives, and the collapse of so many others.